2020
DOI: 10.1038/s41598-020-70504-1
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of agricultural biomass-ash with CO2

Abstract: This work is part of a study of different types of plant-based biomass to elucidate their capacity for valorisation via a managed carbonation step involving gaseous carbon dioxide (co 2). the perspectives for broader biomass waste valorisation was reviewed, followed by a proposed closed-loop process for the valorisation of wood in earlier works. the present work newly focusses on combining agricultural biomass with mineralised co 2. Here, the reactivity of selected agricultural biomass ashes with co 2 and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 51 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…Torrefaction or mild pyrolysis occurs in the range of 200-350 °C often under atmospheric pressure in the partial or complete absence of oxygen, and produces a solid product commonly referred to as 'torrefied biomass' , but in some cases (e.g., severe torrefaction (270-320 °C, residence time > 30 min), oxidative torrefaction), 26 'biochar' . [27][28][29][30] Some other processes like hydrothermal liquefaction, 31 carbonation or gasification 31,32 may also be employed to produce biochar. Each of these processes may involve certain pre-processing steps to improve the overall performance.…”
Section: Sk Thengane Et Almentioning
confidence: 99%
“…Torrefaction or mild pyrolysis occurs in the range of 200-350 °C often under atmospheric pressure in the partial or complete absence of oxygen, and produces a solid product commonly referred to as 'torrefied biomass' , but in some cases (e.g., severe torrefaction (270-320 °C, residence time > 30 min), oxidative torrefaction), 26 'biochar' . [27][28][29][30] Some other processes like hydrothermal liquefaction, 31 carbonation or gasification 31,32 may also be employed to produce biochar. Each of these processes may involve certain pre-processing steps to improve the overall performance.…”
Section: Sk Thengane Et Almentioning
confidence: 99%
“…5b), and we found that coconut husks (Fig. 6a), an agricultural waste of porous structure and abundant in developing countries 44,45 , could be a promising candidate.…”
Section: Artificial Densification Of Mite Communities By Modifying Th...mentioning
confidence: 84%
“…In addition, our method might have a co-benefit for climate change mitigation. First, the method involved the reuse of coconut husks and agricultural wastes found in abundance in developing countries 44,53 , and therefore might reduce the CO2 emissions from incineration disposal (or burning by householders) of coconut husks 45 . Second, our results showed that the application of coconut husks could also reduce the soil-emitted N2O (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical behaviour, physical and thermo-mechanical properties of reinforced composites have been studied by several researchers [36][37][38][39] to determine their technical and economic feasibility. Several studies have also considered various modifications in terms of treatment, method of production and weight fraction variations of these composites for better properties [40][41][42][43]. One of such modifications is the addition of clay at macro and nano levels, and the effects of clay addition to bio-composites have been studied by many researchers.…”
Section: Introductionmentioning
confidence: 99%